IPTEKS KEBIJAKAN PEMBERIAN FASILITAS KREDIT DI HOTEL FOUR POINTS BY SHERATON MANADO - Baguna, Stacy Englyn; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Management of hospitality industry should determine and apply non-cash payment policy and credit facility policy, as one of the way to increase sales and maximize profit for the company. Credit facility policy by hotel management causes the appearance of receivable. The purpose of this study was to identify credit policy applied at hotel Four Points by Sheraton Manado. Based on the study that has been done, management of hotel Four Points by Sheraton Manado has determine several policies for companies that want to get credit facility. The policies consider these four elements: Credit period, Credit standards, Collection policy, and Cash discount. Suggestion for each departments related to sales cycle is to understand and follow the Standard Operating Procedure (SOP) while performing their tasks.Keywords : Credit, Hotel, Account Receivable, Operational Activities, Tourism